Estudo do 'menor carente' na perspectiva da política da Fundação Nacional do Bem-Estar do Menor (FUNABEM) - Cabral, Maria Angela Varella (1982)
This thesis presents a research on a pedagogic policy towards he1p1ess minore It was developed at CENTRO DE REEDUCAÇÃO FEMININO (CRF), an institution responsab1e for the reeducation of female minor, wich integrates the SISTEMA NACIONAL DE ATENDIMENTO AO MENOR, through its cor responding state institution (IESBEM - INSTITUTO ESP!RITO SANTENSE DO BEM-ESTAR DO MENOR). CRF is in charge of 13 to 18 years old female teenagers, who are there boarding due to anti-social behavior. The research was done from may/1980 to november/ ~98l and data were' collected: reading and analysing official papers; interviewing minors and their sponsors at the instituion (CRF); observing and participating on daily activities. Data were colected in order to verify: a) whether the official national pedagogic policy of FUNABEM, implemented at CRF is the 'promised pedagogy' i b) whether the implementation of this policy has contributed to the achievement of the main objective proposed by the national system; i.e, the reeducation and resocialization of the underaged. Based on impirical observation at CRF, conclusion indicates that the institutionalization process is powerless to solve, through reeducation and resocialization such huge socia-l problem of the helpless and mislead underaged. The mislead and the anti-social minors behavior are the result of strategies to survive found by minors toprotect themselves and their social group of shom they are active participants. As best as the reeducation and resocialization policy may be, as a proposal, it conceals the tendency of the political-social-economic system to maintain will protected the interests of the dominant society. Through reeducation and resocialization, this society expects to live together with rehabilitated minors and as FOUCAULT says, 'docile and useful'. This is what the society desires.